Gas leakage and distribution characteristics of methyl bromide and sulfuryl fluoride during fumigations in a pilot flour mill - Chayaprasert, Watcharapol; Maier, Dirk E.; Subramanyam, Bhadriraju; Hartzer, Michelle (My University, 2013)
The half-loss time (HLT) is used as an indicator to quantify gas leakage rates during methyl bromide (MB) and sulfuryl fluoride (SF) fumigations. Comparisons of HLTs between three MB and three SF fumigations were quantified in the Hal Ross pilot flour mill, Department of Grain Science and Industry, Kansas State University, USA. The sealing quality or gas tightness of the mill before each fumigation was verified by a pressurization test. Fumigant concentrations during the six fumigations were monitored continuously at 30 locations among the five mill floors during the 24 h fumigation period. A weather station on the mill roof monitored barometric pressure, wind speed and direction, temperature, and relative humidity. A data logger on each mill floor recorded temperature and relative humidity. The pressurization test showed that the relationship between airflow rate and building static pressure varied among the fumigations despite the same areas being sealed by two separate fumigation service providers due to environmental conditions not being identical among the fumigations. Concentrations of both fumigants within the mill ranged from 2 to 7 g/m³ . The observed HLTs for the MB and SF fumigations were in the range of 3.61 to 28.64 h and 9.97 to 31.65 h, respectively, and were inversely related only to wind speeds during fumigation and not any other environmental conditions recorded. In our study, the fumigant leakage rate was found to be predominantly a function of wind speed rather than inherent gas characteristics of MB and SF.
Keywords: Structural fumigation; Sealing quality; Leakage rates; Gas dynamics; Half-loss time; Wind speed